2018
DOI: 10.1177/1534508418781010
|View full text |Cite
|
Sign up to set email alerts
|

Variance and Reliability in Special Educator Observation Rubrics

Abstract: This study describes the development and initial psychometric evaluation of the Recognizing Effective Special Education Teachers (RESET) observation instrument. The study uses generalizability theory to compare two versions of a rubric, one with general descriptors of performance levels and one with item-specific descriptors of performance levels, for evaluating special education teacher implementation of explicit instruction. Eight raters (four for each version of the rubric) viewed and scored videos of expli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…In studies to validate content-specific rubrics in reading and math, our results have reported teacher ability centered at −.35 logits (range −1.08 to .38) on a reading comprehension rubric (E. S. Johnson, Moylan, Crawford, & Zheng, 2019), and teacher ability centered at −.05 logits (range −1.73 to 1.37) on a math instruction rubric (Crawford et al, 2019). A direct comparison is not currently possible, as these studies involved different teachers and different raters, but further research investigating special education teachers’ scores using an EI rubric as compared to a content-specific rubric in reading or math, and examining the relationship between teacher performance and student outcomes with the various teacher observation instruments could provide useful information about which protocols provide the most relevant information about a teacher’s performance and the subsequent impact on student outcomes.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…In studies to validate content-specific rubrics in reading and math, our results have reported teacher ability centered at −.35 logits (range −1.08 to .38) on a reading comprehension rubric (E. S. Johnson, Moylan, Crawford, & Zheng, 2019), and teacher ability centered at −.05 logits (range −1.73 to 1.37) on a math instruction rubric (Crawford et al, 2019). A direct comparison is not currently possible, as these studies involved different teachers and different raters, but further research investigating special education teachers’ scores using an EI rubric as compared to a content-specific rubric in reading or math, and examining the relationship between teacher performance and student outcomes with the various teacher observation instruments could provide useful information about which protocols provide the most relevant information about a teacher’s performance and the subsequent impact on student outcomes.…”
Section: Discussionmentioning
confidence: 91%
“…Research in teacher observation has shown that teacher performance can vary depending on the time of year and based on the students in class (Mantzicopoulos et al, 2018). However, several studies have reported that between 2 and 4 observations of teachers’ instruction result in reliable estimates of teacher performance (Crawford et al, 2019; Kane & Staiger, 2012). Our findings found very little variability in teacher performance as a result of the lesson suggesting that this may not have been an issue in the current data set.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations